2020
DOI: 10.1155/2020/4063180
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Investigate the Active Compounds and Mechanisms of Musk for Ischemic Stroke

Abstract: Objectives. This study aims to study the material basis and effective mechanism of musk for ischemic stroke (IS) based on the network pharmacology approach. Methods. We collected the chemical components and target gene of musk from the BATMAN-TCM analytical platform and identified ischemic stroke-related targets from the following databases: DisGeNET, NCBI-Gene, HPO, OMIM, DrugBank, and TTD. The targets of musk and IS were uploaded to the String dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68]. Previous network pharmacology studies successfully investigated the polypharmacological properties of herbal drugs by identifying their active compounds and key therapeutic targets and further elucidating the distinct system-level pharmacological effects and mechanisms (e.g., therapeutic modulation of biological processes such as proliferation, apoptosis, cell cycle regulation, angiogenesis, oxidation and reduction, insulin metabolism, and inflammation) for the treatment of various diseases, including cancer, diabetes, arthritis, and ischemic stroke, which are exerted by the synergistic interplay between multiple compounds and targets contained in herbal drugs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In the present network pharmacology study, we aimed to uncover the molecular mechanisms that underlie the analgesic properties of JGd with a system's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68]. Previous network pharmacology studies successfully investigated the polypharmacological properties of herbal drugs by identifying their active compounds and key therapeutic targets and further elucidating the distinct system-level pharmacological effects and mechanisms (e.g., therapeutic modulation of biological processes such as proliferation, apoptosis, cell cycle regulation, angiogenesis, oxidation and reduction, insulin metabolism, and inflammation) for the treatment of various diseases, including cancer, diabetes, arthritis, and ischemic stroke, which are exerted by the synergistic interplay between multiple compounds and targets contained in herbal drugs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In the present network pharmacology study, we aimed to uncover the molecular mechanisms that underlie the analgesic properties of JGd with a system's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In the East, Chinese herbal medicine has been used to treat stroke for thousands of years due to its cheap and easily available resources. A variety of Chinese patent medicines can be used to treat IS, and many scholars have conducted research on medicines such as Tribulus Terrestris [ 27 ], Shuxuening injection [ 28 , 29 ], baicalin [ 30 ], geniposide [ 31 ], Chuanxiong-Chishao [ 32 ], Musk [ 33 ], Nao An capsule [ 34 ], Deng-Zhan-Xi-Xin injection [ 35 ], scutellarin [ 36 ], and Qingkailing injection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These activities and its underlying mechanisms are involved in promoting cell proliferation, ameliorating the loss of cell viability, preventing mitochondrial membrane potential collapse, lactate dehydrogenase, Ca 2+ overload, ROS generation, and reducing the release of inflammatory factors, such as IL-1β, TNF-α, prostaglandin E2, and myeloperoxidase (Liu et al, 2017;Surinkaew et al, 2018;Zhou et al, 2020). Wei et al (2012) and Zhang et al (2020) reported that muscone can inhibit apoptosis via inhibiting expression of caspase 8 and Fas in the cortex and stimulate neural stem cells proliferation transforming them into neurons in ischemia/reperfusion rats. Muscone has also been suggested to mitigate hyperglycemia-induced Schwann cell autophagy and apoptosis partially by activating the Akt/mTOR signaling pathway (Dong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%